PENGARUH PENGGUNAAN MEDIA PODCAST TERHADAP KEMAMPUAN MENYIMAK SISWA KELAS X SMK NEGERI 1 POGALAN - Widyatama, Wahyu; Firmansyah, Eka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of podcast media on listening skills in the Indonesian language subject for Grade X students at SMK Negeri 1 Pogalan. This research employs a quantitative approach with an experimental research type and utilizes a Quasi-Experimental design in the form of The Nonequivalent Pretest-Posttest Control Group Design. The sampling technique used in this study is purposive sampling, with a total sample consisting of class X AKT 1 (36 students) as the experimental group and class X AKT 2 (36 students) as the control group. Data collection techniques used in this study are tests and observation sheets. Data analysis involves both descriptive and inferential statistical analysis techniques. Hypothesis testing in the inferential statistical analysis utilizes the Paired Sample T-test. The conclusion of this study is that podcast media significantly influences the improvement of listening skills in the Indonesian language subject among Grade X students at SMK Negeri 1 Pogalan.